Case report: Intracoelomic neoplastic mass of undetermined origin in an Asia minor spur-thighed tortoise (Testudo graeca ibera) - François, Camille; Paillusseau, Clément; Bagatella, Stefano; Origgi, Francesco; Schilliger, Lionel (Frontiers in Veterinary Science, 2023)
This article describes the diagnostic, treatment and attempted characterization of a neoplasia of undetermined origin in a Asia minor spur-thighed tortoise. A 21-year-old male Asia minor spur-thighed tortoise (Testudo graeca ibera) was admitted for a 4-month history of diarrhea, and a 2-month history of anorexia and lethargy. Physical examination revealed a firm midcoelomic mass in the right prefemoral fossa. Blood biochemistry indicated hypocalcemia and mild elevation of aspartate aminotransferase. Supportive care was administered in the form of heating, baths, and calcium injections. Ultrasound examination of the coelomic cavity revealed a 6-cm diameter, highly vascularized mass with liver-like echogenicity. Neoplasia was suspected, and endoscopy was performed, revealing a brown circumscribed mass with smooth edges. Surgical removal of the mass was evaluated by CT scan and achieved via a plastrotomy; however, the patient died 1 day post-surgery. The mass was located on the dorsal right side of the coelomic cavity in the anatomic location of the right testicle. Histopathology revealed neoplastic cells organized in packets supported by fibrous septa. Neoplastic cells showed moderate and inconsistent positive immunohistochemical labeling for S100 and NSE, and negative immunohistochemical labeling for pan-cytokeratin, vimentin, CD3, CD79a, chromogranin A, and synaptophysin. The prominent histological and anatomical characteristics of the mass indicated a possible testicular or neuroendocrine (e.g., adrenal gland) origin. Due to inconclusive immunohistochemical profiles and poorly differentiated neoplastic cells, only a final diagnosis of intracoelomic malignant tumor of undetermined origin could be established. This case underscores the difficulties encountered in achieving definitive diagnoses of neoplastic diseases in reptile medicine.